Riociguat for pulmonary arterial hypertension and chronic thromboembolic pulmonary hypertension: Results from a phase II long-term extension study. (July 2017) - Halank, Michael; Hoeper, Marius M.; Ghofrani, Hossein-Ardeschir; Meyer, F. Joachim; Stähler, Gerd; Behr, Jürgen; Ewert, Ralf; Fletcher, Monique; Colorado, Pablo; Nikkho, Sylvia; Grimminger, Friedrich
Abstract: Background: Riociguat was well tolerated and improved exercise and functional capacity in patients with pulmonary arterial hypertension (PAH) and inoperable chronic thromboembolic pulmonary hypertension (CTEPH) in a 12-week Phase II trial. We present final data from the long-term extension phase of this study. Methods: During this multicenter, open-label, uncontrolled long-term extension study, riociguat dose could be changed at the physician's discretion (range 0.5–2.5 mg three times daily). The primary outcome was long-term safety and tolerability of riociguat; secondary outcomes included 6-minute walking distance, World Health Organization functional class, survival, and clinical worsening-free survival. Results: Sixty-eight patients (inoperable CTEPH, n = 41; PAH, n = 27) entered the long-term extension. Median treatment duration at the final data cut-off was 77 months. The most common adverse events were nasopharyngitis (57%) and peripheral edema (37%). Three patients (4%) experienced serious adverse events of hemoptysis: two moderate, one severe, none fatal or considered drug-related. At Month 48, 6-minute walking distance increased from baseline by 69 ± 105 m, and World Health Organization functional class improved/stabilized/worsened versus baseline in 50/45/5% of patients. Three-year survival and clinical worsening-free survival were 91% and 49%, respectively (with patients censored if they withdrew without experiencing an event). Starting a new PAH treatment was the most frequent clinical worsening event. Conclusions: Improvements in exercise and functional capacity were maintained at 4 years in patients remaining on treatment, with no new safety signals identified. These data support riociguat as a long-term treatment option for PAH and inoperable CTEPH. Trial registered at: ClinicalTrials.gov . Registration number: NCT00454558 . Highlights: We performed a Phase II long-term extension of riociguat in PAH and CTEPH patients. Over a median treatment duration of >6 years, no new safety signals were identified. Improvements in 6MWD and WHO FC persisted at 4 years. Survival (91% at 3 years) was comparable in other riociguat long-term studies. Riociguat is a favorable long-term treatment for patients with PAH and CTEPH.